Trends and socioeconomic inequalities of recommended antenatal care services utilization in Ethiopia: A decomposition analysis using Ethiopian nationwide Demographic Health Surveys 2011-2019. - Yawkal Tsega; Abel Endawkie; Gebeyehu Tsega; Asnakew Molla Mekonen; Yeshimebet Ali Dawed; Chad Stecher (PLoS ONE)
Background Antenatal care (ANC) services are essential to reduce maternal and newborn morbidity and mortality rates. However, the trends and socioeconomic inequality of utilizing recommended ANC services has not been well studied in Ethiopia. Therefore, this study aims to investigate the trends and socioeconomic disparities in receiving recommended ANC services among Ethiopian women. Methods This study used recent Ethiopian Demographic Health Surveys (EDHS) conducted in 2011, 2016, and 2019. Binary logistic regression model was employed to assess the association between receiving the recommended ANC services and explanatory variables and socioeconomic disparities were estimated through concentration index (CIX) analysis. Moreover, Wagstaff approach was used to decompose the relative CIX to the contribution of explanatory variables for the observed disparities. Results This study found that 37.37% (95%CI: 36.46-38.28%) of mothers utilized the recommended ANC services in Ethiopia. The trend in the coverage of recommended ANC services increased from ~ 30% in 2011 to 44.70% in 2019. Mother's age and education, household wealth status, distance of the nearest health facility, and experiencing domestic abuse (i.e., wife beating) were significantly associated with utilization of recommended ANC services. The relative estimated CIX for wealth index, mothers education, Ethiopian administrative regions, and residence were 0.15 (P < 0.001), 0.14 (P < 0.001), 0.07(P < 0.001), and -0.11(P < 0.001), respectively. Wealth status of the households contributed for almost two-thirds (66.58%) of the observed disparity in recommended ANC service utilization across wealth categories. Conclusion The study revealed that Ethiopian women's utilization of recommended ANC services was unequal by their socioeconomic classes, with better off women more likely to utilize the recommended ANC services than worse off women. Hence, the responsible body should improve the access and quality of antenatal care services for underprivileged women in Ethiopia.